2014
DOI: 10.1080/17452007.2014.925418
|View full text |Cite
|
Sign up to set email alerts
|

Delivery methods for a multi-disciplinary architectural engineering capstone design course

Abstract: The Faculty of Engineering at University of New Brunswick has developed a Master of Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…co-located) teams, and attempt to understand the factors influencing the performance of a virtual team. However, given the dynamic of a virtual team, variability of implementation context and approaches adopted (Solnosky et al, 2014), the performance of the team over a longer time, its influencing factors and impact are difficult to assess objectively (Becerik-Gerber et al, 2012;Soetanto et al, 2014). O'Brien et al (2003) and Becerik-Gerber et al (2012) found that remote collaboration is not always successful and often less effective than face-to-face offline meetings.…”
Section: The Need For Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…co-located) teams, and attempt to understand the factors influencing the performance of a virtual team. However, given the dynamic of a virtual team, variability of implementation context and approaches adopted (Solnosky et al, 2014), the performance of the team over a longer time, its influencing factors and impact are difficult to assess objectively (Becerik-Gerber et al, 2012;Soetanto et al, 2014). O'Brien et al (2003) and Becerik-Gerber et al (2012) found that remote collaboration is not always successful and often less effective than face-to-face offline meetings.…”
Section: The Need For Researchmentioning
confidence: 99%
“…Several scholars have published lessons learnt from their implementation in their classes, but these are somewhat piecemeal and do not cover activities comprehensively. This is mainly due to the variability of implementation (Solnosky et al, 2014). One recent example, Lee et al (2013) provides guidelines for integration of BIM in construction engineering and management education.…”
Section: Guidance For Implementing Collaborative Design Projectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors included: (1) general awareness [37][38][39][40]; (2) technical field [41][42][43]; (3) human resource [44][45][46]; (4) cost field [3,4]; (5) university-and-institution cooperation [47][48][49]; (6) policy areas [23,50,51]; and (7) industrial management system [52][53][54]. The first group of factors is reflected in some well-recognized, construction industrialization policies in regard to building kinds and company's stance [55][56][57][58].…”
Section: Challenges In Industrializationmentioning
confidence: 99%